PROMIS Depression and Anxiety in shoulder surgery patients. (1st April 2022) - Baker, Mitchell; Albelo, Fernando; Zhang, Tina; Schneider, Matheus Boettcher; Foster, Michael J.; Aneizi, Ali; Hasan, S. Ashfaq; Gilotra, Mohit N.; Henn, R. Frank
Abstract : Aims: The purpose of this study was to assess the prevalence of depression and anxiety symptoms in patients undergoing shoulder surgery using the National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) Depression and Anxiety computer adaptive tests, and to determine the factors associated with more severe symptoms. Additionally, we sought to determine whether PROMIS Depression and Anxiety were associated with functional outcomes after shoulder surgery. Methods: This was a retrospective analysis of 293 patients from an urban population who underwent elective shoulder surgery from 2015 to 2018. Survey questionnaires included preoperative and two-year postoperative data. Bivariate analysis was used to identify associations and multivariable analysis was used to control for confounding variables. Results: Mean two-year PROMIS Depression and Anxiety scores significantly improved from preoperative scores, with a greater improvement observed in PROMIS Anxiety. Worse PROMIS Depression and Anxiety scores were also significantly correlated with worse PROMIS Physical Function (PF) and American Shoulder and Elbow Surgeons scores (ASES). After controlling for confounding variables, worse PROMIS Depression was an independent predictor of worse PROMIS PF, while worse PROMIS Anxiety was an independent predictor of worse PROMIS PF and ASES scores. Conclusion: Mean two-year PROMIS Depression and Anxiety scores improved after elective shoulder surgery and several patient characteristics were associated with these scores. Worse functional outcomes were associated with worse PROMIS Depression and Anxiety; however, more severe two-year PROMIS Anxiety was the strongest predictor of worse functional outcomes. Cite this article: Bone Joint J  2022;104-B(4):479–485.